If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -16 + -15 = (45) Reorder the terms: -16 + -15 + 11y = (45) Combine like terms: -16 + -15 = -31 -31 + 11y = (45) -31 + 11y = 45 Solving -31 + 11y = 45 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '31' to each side of the equation. -31 + 31 + 11y = 45 + 31 Combine like terms: -31 + 31 = 0 0 + 11y = 45 + 31 11y = 45 + 31 Combine like terms: 45 + 31 = 76 11y = 76 Divide each side by '11'. y = 6.909090909 Simplifying y = 6.909090909
| -9x^2+6x+3=0 | | y=a | | 16x-4=4(2p-3) | | 6=13(x+2) | | 18x+15(5+40)=46 | | 3a+12=3a+6 | | 36n^2+12n=0 | | 2+3n-1n=-7 | | (s+6)/(3)=9 | | S=1800n-360 | | 4x+3=-560 | | 20=-7u+5(u+8) | | 7a+15b=-73 | | -6y^2z^5= | | 5p-7=-5+43 | | .2x+20=9x-36 | | 8p+54=6 | | 3x+9=42+2x | | 8x+11-3x=2b+2 | | 3x=16x+12 | | 4x+9+5x=81 | | (2x^2+3y^3)(2x^2+3y^3)= | | abs(4x-3)+2=8 | | 48n^2+56n=0 | | -8+2(8x+9)= | | 12d^2=1.89 | | -6n-20=-2n+4(1-30n) | | 16=8m-(5m+2) | | x-12=5x+4 | | .3x+33=5x+13 | | 9k^2-4=0 | | -(r-10)= |